Spontaneous Rupture of Bicornuate Uterus Caused by Levorotation Due to Congenital Band - Jain, M; Tripathi, R; Jain, S; Verma, A; Bajpai, N (Nepal Journal of Obstetrics and Gynaecology, 2014)
Rupture of gravid uterus due to torsion is a rare obstetric complication. The uterus has little mobility and is firmly held in place by its supports which resist any tendency of torsion. We are reporting a case of bicornuate uterus with rupture of left horn due to inability of malformed uterus to expand and axial torsion around one of its horns held by congenital band. Band was dissected and ruptured left horn excised, hemostasis was secured leaving the nonruptured nongravid horn of uterus intact. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 57-59 DOI: http://dx.doi.org/10.3126/njog.v8i2.9773